Hubungan Keragaman Konsumsi Pangan dan Sanitasi Lingkungan terhadap Kejadian Stunting: The Relationship Between Dietary Diversity and Environmental Sanitation With Stunting Occurrence - Lawini, Teni; Nisa, Ainun; Hekmah, Nurul; Norhasanah (JURNAL GIZI DAN KESEHATAN, 2024)
Stunting is a condition in which a toddler has a height or length that is below the average for their age. Stunting is a nutritional health problem that indicates chronic malnutrition in toddlers. Stunting has long-term implications, such as reduced cognitive and physical development, lower performance in tests, and lower per capita household expenditures. This study aims to analyze the relationship between dietary diversity, environmental sanitation, and the occurrence of stunting in children. Data from a sample size of 58 toddlers were collected in the working area of the Pasar Panas Health Center, Benua Lima District, Barito Timur Regency. The study was conducted from December 2022 to March 2023. The analysis was performed using the Spearman Rank Correlation method. The results of the analysis showed that there was no significant relationship between dietary diversity and the occurrence of stunting (p=0.317, correlation coefficient = 0.134). However, there was a significant relationship between family environmental sanitation, availability of clean water (p=0.013, correlation coefficient=0.326), waste disposal (p=0.000, correlation coefficient=0.478), and household environmental conditions with the occurrence of stunting in children (p=0.003, correlation coefficient=0.387). Poor environmental sanitation increases the risk of infections and can hinder the growth and development of children. Therefore, access to adequate clean water, proper waste management, and good household environmental conditions are important in preventing the occurrence of stunting in children.